Membangun Lingkungan Sekolah Kolaboratif Melalui Kepemimpinan Bersama (Shared Leadership) - Lisma Yenti, Filda; Nurzen .S, M. (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
This research aims to evaluate and understand how schools build a collaborative environment through shared leadership at SDN 030/XI Sungai penih, thereby creating an inclusive and productive learning culture. This research was conducted with a qualitative descriptive approach, using a qualitative research type. The method applied involves a descriptive approach, with data collection through observation, interviews and documentation. For data analysis, data reduction techniques, data presentation, verification and conclusion drawing are used. The results of the study show that building a collaborative school environment through shared leadership has gone well at SDN 030/XI Sungai Banyak, showing indicators such as implementing transparency and open communication. As a result, schools become more adaptive, responsive to the needs of all parties, and able to achieve educational goals more effectively. This research has a significant contribution in providing an understanding that the application of shared leadership not only encourages the creation of strong collaboration in the school environment, but also improves the quality of collective decision making. The implications of this research indicate that the shared leadership model can be a strategic approach to creating an inclusive and productive learning culture, as well as providing a relevant framework for other schools wishing to increase effectiveness and inclusivity in their educational environment.